2017
DOI: 10.1080/02770903.2017.1350968
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depressive symptoms in uncontrolled asthmatics

Abstract: Subjects with depressive symptoms have significantly less knowledge of their disease and poorer QOL compared to those without depressive symptoms. Evaluating depressive symptoms in subjects with asthma will provide a more complete picture of their overall condition. The role of asthma education on depressive symptoms in this population needs to be further investigated. The effect of QOL on treating depression in asthma patients also needs to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…It was further observed that 26.8% of asthma patients had moderate to severe depression. In studies conducted before the pandemic, the prevalence of depression in asthma patients was significantly higher than in the healthy group [7,17,22,23]. In fact, the prevalence of depression we found in asthma patients during the pandemic was considerably higher than in studies conducted before the pandemic.…”
Section: Discussioncontrasting
confidence: 52%
“…It was further observed that 26.8% of asthma patients had moderate to severe depression. In studies conducted before the pandemic, the prevalence of depression in asthma patients was significantly higher than in the healthy group [7,17,22,23]. In fact, the prevalence of depression we found in asthma patients during the pandemic was considerably higher than in studies conducted before the pandemic.…”
Section: Discussioncontrasting
confidence: 52%
“…On the other hand, depression is cited as factor affecting patients' subjective evaluation of asthmatic symptoms; it reduces the health-related quality of life, worsens asthma management, correlates with asthma severity, and affects the asthma control status and treatment adherence [20,21]. Some findings suggest that adult patients with depressive symptoms may have a nearly twice higher risk of asthma onset than those without depression [14,22]. A longitudinal observational study by Brunner et al [23] points to depression as a marker of risk for incident adult-onset asthma in middle-aged adults.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training has shown a beneficial effect on the symptoms of anxiety and depression in meta-analyses, with greatest effects on depression [58]. A Cochrane review of exercise training in asthma concluded that exercise training-related improvements in quality of life may result in improved psychosocial well-being [59] Anxiety and depression are prevalent in asthma, particularly within difficult and severe asthma [60], and depression is related to higher levels of hospital admission, corticosteroid use [61] and poorer quality of life [62].…”
Section: Potential Mechanisms To Explain the Anti-inflammatory Effectmentioning
confidence: 99%